A Critical Perspective on Testimonial Injustice: Interrogating Witnesses' Credibility Excess in Criminal Trials - Jasmine Gonzales Rose (Quaestio Facti)
This paper offers a critical race theory perspective on the testimonial injustice experienced by racially minoritized criminal defendants in evidential practice. It builds off Federico Picinali’s paper, inter alia, substantiating how minoritized criminal defendants experience testimonial harm through credibility deficit, by exploring epistemic injustice to the same when prosecutorial witnesses receive identity-based credibility excess. It argues that in an adversarial criminal legal system, the testimonial injustice of credibility excess afforded racial in-group prosecutorial witnesses should be considered in tandem with the testimonial injustice of credibility deficit imposed on racial out-group defendants. Only then can the epistemic harm and resultant unfairness at trial for defendants be fully assessed. The paper advocates for expanding the definition of testimonial injustice to encompass the epistemic wrong of socially biased credibility excess and “transferred epistemic harm.” In instances of transferred epistemic harm, the harm inflicted by an epistemic wrong impacts the speaker’s interlocutor rather (or more) than the speaker themselves.